2020
DOI: 10.1002/slct.201904098
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry‐Like Core‐Shell Structured C@MnO2 as Electrode Material for Li–Ion Batteries and Pseudo‐Capacitors

Abstract: In present work, mulberry-like core-shell structured C@MnO 2 was synthesized as electrodes for Li-ion batteries and pseudocapacitors. Benefiting from the nanoporous shell and conductive carbon core that improve the ion transference and conductivity, the C@MnO 2 delivers excellent electrochemical performance in terms of a stable lithium storage capacity of 553 mAh g À 1 after 250 cycles under 0.5 A g À 1 and a high capacitance up to 274.44F g À 1 under 1 A g À 1 in 6 M KOH and the capacity retention is 90.2% af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…This may have resulted from the MnO 2 (theoretical capacity: 1230 mA h g –1 ) coating layer in the Ni 3 S 2 @MnO 2 nanorod arrays (8.3% of MnO 2 in Ni 3 S 2 @MnO 2 -2, Figure S7). The increased capacity for Ni 3 S 2 @MnO 2 -2 with surface coating can be assigned to the electrochemical reaction between MnO 2 and lithium which can be observed from the platform at ∼0.3 V (Figure d). The Coulombic efficiency of Ni 3 S 2 @MnO 2 -2 is also increased from 81.6% to 84.2% in comparison with the pure Ni 3 S 2 , demonstrating that the MnO 2 coaxial layer reduces the loss of irreversible capacity significantly. Specific capacities at different discharge rates were calculated based on the discharge curves (Figure e).…”
Section: Resultsmentioning
confidence: 91%
“…This may have resulted from the MnO 2 (theoretical capacity: 1230 mA h g –1 ) coating layer in the Ni 3 S 2 @MnO 2 nanorod arrays (8.3% of MnO 2 in Ni 3 S 2 @MnO 2 -2, Figure S7). The increased capacity for Ni 3 S 2 @MnO 2 -2 with surface coating can be assigned to the electrochemical reaction between MnO 2 and lithium which can be observed from the platform at ∼0.3 V (Figure d). The Coulombic efficiency of Ni 3 S 2 @MnO 2 -2 is also increased from 81.6% to 84.2% in comparison with the pure Ni 3 S 2 , demonstrating that the MnO 2 coaxial layer reduces the loss of irreversible capacity significantly. Specific capacities at different discharge rates were calculated based on the discharge curves (Figure e).…”
Section: Resultsmentioning
confidence: 91%
“…Qi et al recently reported a mulberry-like core-shell structured C@MnO 2 . The material shows high capacitance up to 274.44 F g −1 under 1 A g −1 in 6 M KOH and the capacity retention is 90.2% after 5000 cycles [66].…”
Section: Conversion Oxidesmentioning
confidence: 99%
“…One such approach is the synthesis of nano-scaled MO x /TMO x . [21][22][23] It is well understood that electrochemical features, such as catalysis, charge storage, and conductivity, are largely dependent on the surface area of the material. Nanoparticles (NPs), nanocomposites, and nanomaterials offer greater surface area for competent electrochemical reactions to enhance the energy storage and energy generation capacities of electrodes.…”
Section: Introductionmentioning
confidence: 99%